PELATIHAN PEMBUATAN AKUARIUM IKAN HIAS BAGI GURU-GURU SD DAN LOMBA MEWARNAI BIOTA LAUT DALAM MENDUKUNG PENGEMBANGAN MEDIA PEMBELAJARAN DI SDK. STA. MARIA ASSUMPTA: PELATIHAN PEMBUATAN AKUARIUM IKAN HIAS BAGI GURU-GURU SD DAN LOMBA MEWARNAI BIOTA LAUT DALAM MENDUKUNG PENGEMBANGAN MEDIA PEMBELAJARAN DI SDK. STA. MARIA ASSUMPTA - Saraswati, Suprabadevi (Jurnal Pengabdian Perikanan Indonesia, 2025)
Elementary School (abbreviated SD) is the basic level of formal education in Indonesia. Educational development in introducing the environment certainly requires learning media to develop the creativity of elementary school students. The need for learning media for elementary school students when the community service team visited, still did not touch on the aspects of the fisheries and marine environment. This community service activity aims to provide training to teachers at SDK STA Maria Assumpta, Kupang City to improve their skills in developing learning media in the form of ornamental fish aquariums, and marine biota coloring competition activities in introducing and increasing the knowledge of grade 1 students. The method used in implementing the training activities, namely the demonstration method (training/direct demonstration) of how to make an aquarium to teachers at SDK STA Maria Assumpta, Kupang City which includes several specific stages including the preparation of tools and materials, the stage of conveying the procedure for making an ornamental fish aquarium and the stages of making an ornamental fish aquarium; while for the coloring competition activity, it will begin with an introduction to marine biota on the coast and sea of ​​NTT Province, followed by coloring activities and assessment of coloring results for students in the therapy class category. The Community Service Program activities are expected to provide benefits between the two institutions, where for the university, in this case the Study Program, it can be used as a benchmark for the development of the Tridharma of higher education and for the SDK STA Maria Assumpta institution in developing the quality and standard of education for elementary school children.